2019
DOI: 10.2807/1560-7917.es.2019.24.31.1800357
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter species prevalence, characterisation of antimicrobial resistance and analysis of whole-genome sequence of isolates from livestock and humans, Latvia, 2008 to 2016

Abstract: Background Campylobacter is the main cause of bacterial gastroenteritis worldwide. The main transmission route is through consumption of food contaminated with Campylobacter species or contact with infected animals. In Latvia, the prevalence of campylobacteriosis is reported to be low (4.6 cases per 100,000 population in 2016). Aim To determine prevalence, species spectrum and antimicrobial resistance (AMR) of Camp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 26 publications
10
34
1
Order By: Relevance
“…The finding also revealed that C. coli isolate recovered from aquatic milieu was closely related with those from other sources and this result corresponds with the report of [ 53 ]. Detection of genotypic relatedness among some C. coli and C. jejuni isolates recovered from aquatic milieu and meat sources confirmed that livestock and poultry are sources of environmental spread of Campylobacter species and these results is in accordance with the report of [ 54 ]. Genetic diversity is one of the different mechanisms that helps pathogens to thrive in unfriendly circumstances within the environment or in the host given them the ability to colonize multiple hosts [ 55 ].…”
Section: Resultssupporting
confidence: 90%
“…The finding also revealed that C. coli isolate recovered from aquatic milieu was closely related with those from other sources and this result corresponds with the report of [ 53 ]. Detection of genotypic relatedness among some C. coli and C. jejuni isolates recovered from aquatic milieu and meat sources confirmed that livestock and poultry are sources of environmental spread of Campylobacter species and these results is in accordance with the report of [ 54 ]. Genetic diversity is one of the different mechanisms that helps pathogens to thrive in unfriendly circumstances within the environment or in the host given them the ability to colonize multiple hosts [ 55 ].…”
Section: Resultssupporting
confidence: 90%
“…High concordance (97.5%) was shown to occur between the presence of AMR determinants in WGS data and phenotypic resistance among 528 C. jejuni and C. coli isolates from England and Wales (Painset et al, 2020). Similar results were recently reported from Latvia (Meistere et al, 2019).…”
Section: Introductionsupporting
confidence: 83%
“…Only a few Campylobacter isolates possessed genes associated with aminoglycoside (e.g., gentamicin or streptomycin) resistance (approximately 11% had aph(3')-III or aadE-Cc genes). However, previous studies have shown that the prediction of resistance against aminoglycosides is not always straightforward from WGS data using currently available tools (Meistere et al, 2019). In this study, the obtained phenotypic rate of resistance to gentamicin was slightly lower compared to the genotypic rate, confirmed in 2 out of 43 isolates (CI 95%: 1.3-15.5%).…”
Section: Discussioncontrasting
confidence: 49%
“…The collection of C. jejuni isolates (n = 420) with assigned MLST genotype from human patients (n = 132), poultry (n = 139), cattle (n = 48) and wild birds (n = 101) were obtained from three previously published studies [5][6][7] (S1 File). Sources with less than 40 strains were discarded.…”
Section: Jejuni Isolatesmentioning
confidence: 99%
“…Multilocus sequence typing (MLST) data has been successfully used for attribution studies to determine potential links between the sources and clinical isolates [4]. Several overview studies have been recently published regarding epidemiology and MLST genotype diversity of C. jejuni in the Baltic countries by Mäesaar et al [5], Meistere et al [6] and Aksomaitiene et al [7]. Although the studies demonstrated overlap between C. jejuni MLST genotypes isolated from human patients and genotypes found in poultry and cattle, there has not been conducted source attribution analyses of clinical Baltic C. jejuni isolates.…”
Section: Introductionmentioning
confidence: 99%